Hypothalamic mediation of reduced GH secretion in diabetic rats: evidence for reduced cholinergic inhibition of somatostatin release - Ismail, I.S.; Lewis, M.; Peters, J.R.; Scanlon, M.F. (Blackwell Publishing, 1995)
The Goto-Kakizaki (GK) rat is a new model of diabetes mellitus and in this study we have characterized the diabetic and growth hormone (GH) secretory status of male GK rats at 6 and 16 weeks of age. We have also investigated the role of endogenous somatostatin (SS) and cholinergic manipulation on the GH responses to GH-releasing hormone (GHRH). GK rats were non-obese with significant fasting hyperglycaemia, hyperinsulinaemia and absent insulin responses to IV glucose. The GH response to GHRH was reduced at 16 weeks compared with normal, age-matched Wistar rats but no differences were observed at 6 weeks. Pretreatment of older rats (16 weeks) with anti-somatostatin antibodies (SS-Ab) significantly increased GH responses to GHRH in both normal and GK groups. Cholinergic augmentation with pyridostigmine (PD) reversed the blunted GH responses to GHRH in older GK rats but had no effect in the normal or young (6 weeks) GK rats. These results indicate that SS release mediates the blunted GH responses to GHRH in GK rats and that reduced hypothalamic cholinergic signalling to the somatostatinergic neurone may mediate the increase in SS release. This view is supported by the results from in vitro studies in which cholinergic muscarinic blockade with pirenzepine (PIR) caused dose-related stimulation of SS release from normal rat hypothalami but was without effect on GK rat hypothalami. The cause of this alteration in hypothalamic function is, at present, unknown.